Mexican Higher Education and the Production of Knowledge - Elida Sánchez Cruz (Ali Khorsandi Taskoh, 2021)
Higher education is a central institution to formulate new responses and novel solutions to current social problems. In this context, the objective of this paper is to evaluate the production of knowledge carried out in the Technological Institutes of Higher Education (TIHE) in Mexico through online documentary research. Considering that most of the research is carried out based on international theories, a national evaluation system was taken into consideration to better understand the production of knowledge in this country. The results show that almost half of the TIHE professors have a BA degree, which make it impossible for them to be part of the national evaluation system and possibly do not have the required training to be producing quality knowledge. Only 2, 151 TIHE professors have the required PhD to participate in the national evaluation system; out of this total, only 769 TIHE professors were nationally recognized. Based on the findings, one can only question the role that TIHE have in the development of the country as an academic institution.